INTELLIGENT INTERACTION VIA CHATBOTS TRANSCENDING THE CURRENT CONSTRUCTS - Samiksha Chitranshi , Pramod Daml (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Purpose: To study the chatbots’ effectiveness in transforming the current business constructs. Research Method: A comparative study of five chatbots in different domains based on the detailed dialogue flows and instant messenger interface with users. Findings: The study provides rating to the selected five chatbots as per their efficacy in interacting with the users. Application: The study would be useful for the business owners of the different domains discussed regarding their investments in chatbots as a cost-effective tool for better customer experience leading to better sales and thereby increased revenues of their business. It would assist chatbot developers for the design factors to be considered while constructing chatbots. It would help future researchers to propose strategies and frameworks to increase customer engagement through chatbots. It would also supply academics with a foundation for further theory building processes regarding chatbot design and engineering.